การประเมินวิธีวิเคราะห์แบบแรงกระทำด้านข้างแยกโหมดที่ถูกปรับปรุงโดยใช้คลื่อนแผ่นดินไหวระยะใกล้รอยเลื่อน - อมรชัย ใจยงค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
While nonlinear response history analysis (NL-RHA) is the most rigourous procedure to estimate seismic demands for buildings, it is not yet practical for use by regular engineers. Thus, the static pushover analysis, which is simpler, but however is an approximate method, has been improved and a modified modal pushover analysis (MMPA) has recetly been proposed with an assumption that structural responses can be estimated by superposition of modes and the responses in higher modes remain elastic. The response in the fundamental mode can be computed by nonlinear static analysis. The study evaluates the accuracy of MMPA and MPA procedures by comparing the story drift demands estimated by MMPA and MPA to those computed by NL-RHA, which is regarded as the exact value. The bias is shown by the ratio of story drifts computed by MMPA or MPA and by NL-RHA and dispersion of the story drift ratios were also examined. The evaluation has been performed on a wide range of frame buildings with heights varying from 3, 6, 9, 12, 15, to 18 stories, having one or two bays, designed by both strong-column weak-beam and weak-column strong-beam philosophy and having different strength levels corresponding to systems with ductility factors equal to 1, 1.5, 2, 4, and 6. The structures were subjected to three types of ground motions: 15 near-fault ground motions both fault-normal and fault-parallel components, 20 large-magnitude small-distance (LMSR) far-fault ground motions, and 3 ground motions recorded on soft-soil sites. The following results have been found: (1) the MMPA procedure generally provides story drift demand estimates that are larger than MPA, while their trends of bias and dispersion are similar, (2) the bias and dispersion of MMPA procedure in weak-column strong-beam frames are significantly larger than in strong-column frames, even if in 3-story frames, largely because of inaccurate target roof displacements in pushover analysis, (3) the bias and dispersion of MMPA procedure in two-bay frames are significantly larger than in one-bay frames, (4) the bias of MMPA procedure in frames subjected to near-fault ground motions is similar to when subjected to LMSR (far-fault) ground motions, but with less tendency to over-estimate story drift demands, and (5) the bias of MMPA procedure in frames subjected to ground motions recorded on soft-soil sites is significantly different from when subjected to LMSR ground motions.